Broadening the Definition of Socially Responsible Marketing. (December 2022) - Ferrell, Linda; Ferrell, O.C.
Laczniak and Shultz developed a literature informed macro and normative definition of socially responsible marketing (SRM) that provides a stage for constructive engagement. The elements of the definition include: corporate citizenship, stakeholder orientation and social/ecological sustainability. While the definition is excellent, we focus on the organizational context of SRM. For a normative definition to be of value in research and practice, a micro and positive-descriptive approach is essential in implementing SRM. The Laczniak and Shultz definition provides a foundation and is not in conflict with an instrumental view of SRM. We reconcile the instrumental and normative approaches to SRM and find these perspectives to be congruent.